Cover Picture: Evaluating Dihydroazulene/Vinylheptafulvene Photoswitches for Solar Energy Storage Applications (ChemSusChem 15/2017). Issue 15 (4th August 2017) - Wang, Zhihang; Udmark, Jonas; Börjesson, Karl; Rodrigues, Rita; Roffey, Anna; Abrahamsson, Maria; Nielsen, Mogens Brøndsted; Moth‐Poulsen, Kasper
Abstract : The Cover picture shows an implementation of molecular solar thermal energy storage (MOST) technology on a large scale. It illustrates how the yellow‐colored dihydroazulene (DHA) is converted into red‐colored vinylheptafulvene (VHF) upon irradiation. The robust nature of this system was demonstrated through multiple energy storage‐and‐release cycles. As a potential candidate for the MOST concept, the photoswitch was evaluated both under simulated sunlight conditions as well as under natural outdoor conditions, demonstrating a possible avenue for future lab‐to‐site transfer. More details can be found in the Full Paper by Wang et al. onpage 3049 in Issue 15, 2017 (DOI:10.1002/cssc.201700679 ).